2000
DOI: 10.1038/sj.ijo.0801102
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of the opinions on weight loss treatments of adult obese patients attending a dietetic clinic

Abstract: OBJECTIVE: To investigate the views and opinions on weight loss treatments of adult obese patients attending a dietetic clinic. DESIGN: Cross-sectional survey. SUBJECTS: 161 adults attending dietetic outpatients clinics in Portsmouth for obesity with a body mass index of at least 30 kgam 2 . MEASUREMENTS: Self-administered questionnaire developed from a series of focus groups with obese adults. Key topics were previous attempts to lose weight, methods used, the role of physical activity and patients' views abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 5 publications
1
30
0
3
Order By: Relevance
“…Comme ces derniers [4], nous trouvons un nombre plus important de sujets ayant recours à l'activité physique chez les hommes, et un nombre un peu plus élevé de sujets ayant recours à des produits pour maigrir chez les femmes. Mais, contrairement à Thompson et Thomas [4], nous constatons que les sujets ayant un IMC plus élevé ont moins souvent recours à l'activité physique. Il est évident que la pénibilité de l'exercice physique augmente avec le poids [10].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Comme ces derniers [4], nous trouvons un nombre plus important de sujets ayant recours à l'activité physique chez les hommes, et un nombre un peu plus élevé de sujets ayant recours à des produits pour maigrir chez les femmes. Mais, contrairement à Thompson et Thomas [4], nous constatons que les sujets ayant un IMC plus élevé ont moins souvent recours à l'activité physique. Il est évident que la pénibilité de l'exercice physique augmente avec le poids [10].…”
Section: Discussionunclassified
“…Dans notre étude, les sujets OB connaissent plus souvent l'existence de tels médicaments que les sujets en SP. De même, Thompson et Thomas [4] observent que les sujets ayant un IMC supérieur à 40 kg/m 2 y ont plus souvent recours ; en revanche, en dehors du critère « rapidité d'action » nous ne trouvons pas de différences sur les autres critères déterminants le recours aux médicaments.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…While weight stigma has been studied in the healthcare context, research on discrimination in this context is more limited. In one sample of obese adults, the majority of respondents reported being regarded "as a second class citizen" in the health care setting (Thompson & Thomas, 2000). In another sample of bariatric surgery candidates, nearly half reported that they had been treated disrespectfully by physicians because of their weight and report being "very upset" by comments their doctor has made about their weight (Anderson & Wadden, 2004).…”
Section: Weight Discrimination In the Healthcare Encountermentioning
confidence: 99%
“…Based on the findings of qualitative research involving 161 obese adults attending dietetic outpatient clinics (Thompson & Thomas, 2000), the majority of respondents (84%) agreed that most medical problems for which they visited clinic were blamed on their weight. Also, those with higher BMI were more likely to agree with the statements; "I am regarded as a second-class citizen" and "chairs are never big enough."…”
Section: Patients' Perception Of Weight Stigma In the Healthcare Settingmentioning
confidence: 99%